2018
DOI: 10.31026/j.eng.2018.07.02
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Circular Perforation on a V-Corrugated Fin Performance under Natural Convection

Abstract: An experimental investigation has been made to study the influence of using v-corrugated aluminum fin on heat transfer coefficient and heat dissipation in a heat sink. The geometry of fin is changed to investigate their performance. 27 circular perforations with 1 cm diameter were made. The holes designed into two ways, inline arrangement and staggered in the corrugated edges arrangement. The experiments were done in enclosure space under natural convection. Three different voltages supplied to the heat sink t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…The results showed that the fin with six circular holes has the maximum effectiveness of 0.965 with weight reduction about 50% lower than solid fin. Hussein 13,14 made an experimental study to investigate the effect of v‐corrugated perforation, and nonperforation fin on the thermal performance of a heat sink under natural convection. Fin geometry, perforations arrangement, and type of material also examined.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that the fin with six circular holes has the maximum effectiveness of 0.965 with weight reduction about 50% lower than solid fin. Hussein 13,14 made an experimental study to investigate the effect of v‐corrugated perforation, and nonperforation fin on the thermal performance of a heat sink under natural convection. Fin geometry, perforations arrangement, and type of material also examined.…”
Section: Introductionmentioning
confidence: 99%